Acute patient-reported intestinal toxicity in whole pelvis IMRT for prostate cancer: Bowel dose-volume effect quantification in a multicentric cohort study. (May 2021) - Bresolin, Andrea; Faiella, Adriana; Garibaldi, Elisabetta; Munoz, Fernando; Cante, Domenico; Vavassori, Vittorio; Waskiewicz, Justina Magdalena; Girelli, Giuseppe; Avuzzi, Barbara; Villa, Elisa; Magli, Alessandro; Noris Chiorda, Barbara; et al.
Highlights: Patient-reported diarrhea and urgency were the most frequent acute symptoms in WPRT. Mild symptoms before radiotherapy are the major predictors. V46 < 80 cc is an efficient constraint in reducing the risk about below 20%. Abstract: Background and purpose: To assess bowel dose-volume relationships for acute patient-reported intestinal symptoms of patients treated with whole-pelvis intensity-modulated radiotherapy (WPRT) for prostate cancer. Materials and methods: Complete data of 415 patients enrolled in a multi institute, prospective trial (#NCT02803086) treated with radical (31%), adjuvant (33%) and salvage (36%) intent at a median dose to pelvic nodes/lymph-nodal area of 53 Gy were available. The most severe changes between baseline and radiotherapy mid-point/end toxicity assessed by Inflammatory Bowel Disease Questionnaire (only Bowel Domain) were considered (ΔIBDQ). The 25th percentile values of these score variations were set as endpoints. DVHs of bowel loops for patients with/without toxicity were compared for each endpoint, having excluded patients with baseline scores <5 (rate ranging between 2% and 7% according to the endpoint): the resulting best dosimetric predictors were combined with selected clinical parameters through multivariate logistic regression (MVA) to derive predictive models. Results: ΔIBDQ ranged between 0.2–1.5 points considering separately each IBDQ symptom. Only four symptoms (IBDQ1 = frequency, IBDQ5 = diarrhea, IBDQ17 = gas passage, IBDQ24 = urgency) showed a median worsening ≥ 1; DVH predicted the risk of worse symptoms for IBDQ5, IBDQ24 and overall Bowel Domain. At multivariable analysis DVHs (best cut-off: V46Gy ≥80 cc) and baseline scores (Odd-Ratio:0.35–0.65) were independently associated to the three end-points. The resulting models were reliable (H&L test: 0.453–0.956), well calibrated (calibration plot: slope = 0.922–1.069, R 2 = 0.725–0.875) and moderately discriminative (Area Under the Curve:0.628–0.669). A bootstrap-based validation confirmed their robustness. Conclusion: Constraining the bowel loops (V46 < 80 cc) may reduce the risk of several moderate intestinal symptoms, with a much greater impact for patients with lower IBDQ baseline scores.